DIMENSI KEADILAN PENGELOLAAN PERIKANAN TANGKAP DALAM PERSPEKTIF OTONOMI DAERAH - Indra Yulianingsih (Universitas Airlangga, 2017)
The enactment of Act No. 23 Year 2014 on Regional Government revised the Article 18 paragraph (1) of Act No. 32 of 2004 and caused the authority of local governments in the exploration and exploitation of resources in the sea area not applicable anymore. The impact of this change is the difficulty of local authorities to ensure the welfare and/or the prosperity of communities in the coastal areas that lead to injustice in the realization of people's constitutional rights. Legal issues discussed in this paper are the principle of distributive justice on the management of fishery resources in the autonomous region and the application of the principle of distributive justice on fisheries management in the autonomous region. The principle of distributive justice in an effort to fisheries management is based on several principles: the principle of utility, justice, solidarity, equity and sustainable development. Distributive justice serves as the basis of government policies to the people. The studies of state policy on regional autonomy could delegate that policy through local governments. This should be an opportunity for the region to manage natural resources in order to accelerate the achievement of well-being, especially in the regions.